Trade liberalisation and the environment : are there legitimate worries? - Upton, Simon (2003)
Identifies three sorts of legitimate environmental concerns viz. environmental impacts in the liberalising country; impacts in countries benefiting from liberalisation; and, global environmental impacts from liberalisation and subsidy removal. Looks at how these concerns might be addressed.